2022
DOI: 10.1021/acsami.1c25019
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Framework-Derived Core–Shell Nanospheres Anchored on Fe-Filled Carbon Nanotube Sponge for Strong Wideband Microwave Absorption

Abstract: Metal−organic frameworks (MOFs) are booming as a promising precursor for constructing lightweight, highefficiency microwave absorbing (MA) material. However, it is still a challenge to rationally design three-dimensional (3D), porous MOF-derived MA materials with a stable structure and strong and wideband MA performance. Herein, a 3D hybrid nanostructure (CNT/FeCoNi@C) comprising MOF-derived magnetic nanospheres and Fe-filled carbon nanotube (CNT) sponge has been controllably fabricated to enhance the absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 61 publications
2
41
0
Order By: Relevance
“…Figure 8i summarizes RL peak values of similar MAMs. Minimum RL value of -42.38 dB can be reached at thickness of 2.4 mm for S-800, which can meet most practical situations [24,25,29,[38][39][40][41][42]. Figure 8j lists EAB of reported MAMs.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 8i summarizes RL peak values of similar MAMs. Minimum RL value of -42.38 dB can be reached at thickness of 2.4 mm for S-800, which can meet most practical situations [24,25,29,[38][39][40][41][42]. Figure 8j lists EAB of reported MAMs.…”
Section: Resultsmentioning
confidence: 99%
“…The curves of ε″ versus ε′ are plotted in Figure g–j. According to the Debye theory, one Debye relaxation process corresponds to one semicircle (Cole–Cole semicircle) , where ε s and ε ∞ are the static permittivity and relative permittivity at the high-frequency limit, respectively. It could be observed that multiple Debye relaxation processes existed in HMCS@f-Fe 2 O 3 - x under an external alternating electric field.…”
Section: Resultsmentioning
confidence: 99%
“…j. According to the Debye theory, one Debye relaxation process corresponds to one semicircle (Cole−Cole semicircle)6,37 …”
mentioning
confidence: 99%
“…Currently, the multi-interface engineering of dielectric materials can promote interfacial polarization. Various core–shell-structured nanocomposites have been designed to enhance EWA properties. Inspired by this idea, rational construction of a BN@carbon core–shell structure may facilitate the attenuation of EW and heat dissipation, while the related research work has not been reported. The core–shell structure ensures a strong contact between the BN and carbon shell.…”
Section: Introductionmentioning
confidence: 99%